Complex Emulsions as an Innovative Pharmaceutical Dosage form in Addressing the Issues of Multi-Drug Therapy and Polypharmacy Challenges - Naresh Yandrapalli (MDPI AG, 2024)
This review explores the intersection of microfluidic technology and complex emulsion development as a promising solution to the challenges of formulations in multi-drug therapy (MDT) and polypharmacy. The convergence of microfluidic technology and complex emulsion fabrication could herald a transformative era in multi-drug delivery systems, directly confronting the prevalent challenges of polypharmacy. Microfluidics, with its unparalleled precision in droplet formation, empowers the encapsulation of multiple drugs within singular emulsion particles. The ability to engineer emulsions with tailored properties-such as size, composition, and release kinetics-enables the creation of highly efficient drug delivery vehicles. Thus, this innovative approach not only simplifies medication regimens by significantly reducing the number of necessary doses but also minimizes the pill burden and associated treatment termination-issues associated with polypharmacy. It is important to bring forth the opportunities and challenges of this synergy between microfluidic-driven complex emulsions and multi-drug therapy poses. Together, they not only offer a sophisticated method for addressing the intricacies of delivering multiple drugs but also align with broader healthcare objectives of enhancing treatment outcomes, patient safety, and quality of life, underscoring the importance of dosage form innovations in tackling the multifaceted challenges of modern pharmacotherapy.